MineMixMusics: Exploring co-creative learning processes in postdigital music education - Viig, Tine Grieg (Nordic Research in Music Education, 2025)
This article investigates how integrating technology and virtual worlds, specifically Minecraft Education, can foster collaborative and creative learning processes in Norwegian music education. The MineMixMusics action research project involved participants creating music videos with their avatars as main characters and music of their own selection. The findings indicate that this project’s approach enhances the development of generative spaces for learning, promoting student engagement, co-creativity, and collaborations. The discussion is anchored in post-critical pedagogy and considers the broader implications for technology and entangled postdigital music classrooms. This study contributes to an ongoing dialogue on the versatility and complexity of music education in a postdigital age.